2014
DOI: 10.1111/cpf.12207
|View full text |Cite
|
Sign up to set email alerts
|

Acute eccentric resistance exercise decreases matrix metalloproteinase activity in obese elderly women

Abstract: The association of ageing with obesity commits elderly women and has been correlated with multiple degenerative processes, which could be occasioned by an enhancing in levels of matrix metalloproteinase-2 and metalloproteinase-9 (MMPs) as well by an cytokine unbalance that included an enhancing on interleukin-6 (IL-6). Furthermore, other factors could be also related to degenerative process, as they could be reduced by eccentric resistance exercise (ERE), which seems particularly important to initiate resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Obese people are known to have an imbalance in inflammatory factors ( Jung and Choi, 2014 ). Nascimento et al (2016) also demonstrated that exercise may result in anti-inflammatory responses by reducing MMP-2 and -9 levels because obese individuals maintain a high inflammatory response, even at rest, as compared with healthy subjects. Therefore, future studies should also examine changes in and the relationships among MMP-2, -9, and inflammatory factors following eccentric exercise in healthy subjects.…”
Section: Matrix Metalloproteinase and Tissue Inhibitor Of Metalloprotmentioning
confidence: 94%
See 3 more Smart Citations
“…Obese people are known to have an imbalance in inflammatory factors ( Jung and Choi, 2014 ). Nascimento et al (2016) also demonstrated that exercise may result in anti-inflammatory responses by reducing MMP-2 and -9 levels because obese individuals maintain a high inflammatory response, even at rest, as compared with healthy subjects. Therefore, future studies should also examine changes in and the relationships among MMP-2, -9, and inflammatory factors following eccentric exercise in healthy subjects.…”
Section: Matrix Metalloproteinase and Tissue Inhibitor Of Metalloprotmentioning
confidence: 94%
“…Similarly Mackey et al (2004) reported that MMP-9 and TIMP-1 levels are significantly increased following eccentric exercise. In contrast, Nascimento et al (2016) reported that MMP-2 and -9 levels actually decrease after eccentric exercise, whereas Madden et al (2011) reported that MMP-9 and TIMP-1 levels remain unchanged after eccentric exercise.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…This finding was extended to skeletal muscle myocytes by Neidert et al (2016), who showed that blocking the MMPs present in whey protein resulted in reduced DPP-IV shedding from the myocyte membrane. This is significant because MMPs can increase with hypoxia (Rohrborn et al 2014) and with hyperglycemia (Death et al 2003;Chang and Vivian Yang 2013) and exercise (Schild et al 2016), and may decline as women age (Nascimento Dda et al 2016).…”
Section: Whey Protein Stimulated Dpp-iv Releasementioning
confidence: 99%